Analysis of Bakery SMEs Performance in Magelang, Indonesia - Yuli Liestyana; Zhafira Rahma Anggit Pratiwi; Yekti Utami (AIBPM Publisher, 2021)
This study analyzed performance of SME bakeries in Magelang, Indonesia by testing entrepreneurial orientation and total quality management. The population in this study was 86 SMEs. The study used purposive sampling technique with the following criteria: (1) SMEs that had implemented TQM. (2) SMEs that are 3 years old or more. Based on these criteria, there are 66 SMEs that are sampled in this study. The data analysis technique used in this study is the Partial Least Square. The results of this study indicate that entrepreneurial orientation has a positive effect on Firm performance, TQM has a positive effect on Firm performance, entrepreneurial orientation has a positive effect on TQM, and TQM positively mediates the effect of entrepreneurial orientation on firm performance.